The impact of meteorological changes on the quality of life regarding thermal comfort in the Amazon region - Santos, Adrian Felipe dos; Moura, Flávio Rafael Trindade; Seruffo, Marcos César da Rocha; Santos, Waldeir Pereira dos; Costa, Gabriel Brito; Costa, Fernando Augusto Ribeiro (Frontiers in Climate, 2023)
The meteorological imbalances in Brazil have strong impacts on the lives of the population across the country, especially in the Amazon region. These impacts extend to meteorological phenomena, such as extreme rainfall, droughts and the increase in temperature in several regions, as well as impacts on health, the economy and, as the object of this study, the quality of life. This presents a study about the impact of meteorological changes on the quality of life in the Amazon region, based on (i) the thermal discomfort index (TDI), (ii) the temperature and humidity index (THI) and (iii) the effective temperature index as a function of the wind (TEFW). For this, meteorological data from the years 2003 to 2021 were used, in which the variables of total precipitation, global radiation, air-dry bulb temperature, maximum temperature in the previous hour, minimum temperature in the previous hour, relative humidity and wind speed. This analysis indicates that for this tropical region, the sensation of mild discomfort is predominant in about 70% of the measurements, noting a certain level of impact on the population's quality of life, in addition to the fluctuation of levels of discomfort during periods of winter in that there are high rates of precipitation. The data control was performed by performing the removal of null data and calculation of monthly and annual averages, because of the compression (average) empty data frames were used to receive the values without losing the indexing of dates. At first, it was considered to use the kriging process to fill in the missing data, however, due to the existence of microclimates in the regions, the data could characterize remote regions in a generalized way, which would make it difficult to understand these data in comparison with the data from the National Institute of Meteorology (INMET, in Portuguese).